DIRECTIONS AND PERSPECTIVES OF SUSTAINABLE DEVELOPMENT OF SCIENTIFIC PERSONNEL TRAINING - Fazliddinov, Shahrukh Sh. (Oriental Journal of Education, 2023)
The sustainable development of the process of training personnel with a scientific degree is an important direction of the modern education system. It is a process that includes the preparation and teaching of undergraduate, graduate, and doctoral students. One of the main directions of sustainable development of this process is the creation and development of scientific schools and laboratories. This is achieved by combining the efforts of leading scientists and researchers in solving current scientific problems and developing new technologies. However, various factors such as financing, ease of education and state support have been studied and analyzed in order to achieve sustainable development of the process of training personnel with a scientific degree.